Pola Relasi Gender dan Ketangguhan Masyarakat Suatu Kajian Gender dalam UMKM di Kecamatan Tanjung Mutiara, Kabupaten Agam - Wahyu Pramono; Jendrius Jendrius; Zeni Eka Putri (Jurnal Sosiologi Andalas, 2020)
Abstract: This study analyzes the pattern of gender relations and community resilience in the development of micro enterprises in Tanjung Mutiara District, Agam Regency. The analysis was carried out at the household and community level by conducting interviews with women entrepreneurs, FGDs with women's micro-business groups and limited observation of the conditions of the living environment and the social context of the South Tiku community. The results showed that in general there was a clear division of labor between men and women. Men are involved in temporary productive activities of women in reproductive activities. As a result, women do a greater variety of jobs with a longer duration than men. Productive businesses carried out by women are considered to be only part of the reproductive ladder, so that male involvement and participation are also very low and make women's burdens more severe. Gender relations at the household and community level are relatively equal, this is because women have access and control over resources and also the values ​​and norms that develop in the community facilitate the creation of equality. However, changes in attitudes that are more gender sensitive to the actor's level have not been followed by changes at the community level. It is recommended that an effort to raise awareness for men both at the household and community level is more gender sensitive. Both efforts to provide assistance to micro-enterprises carried out by women need to be optimized especially for individuals or groups of women who really want to develop their businesses.